Primary cutaneous cryptococcosis due to Cryptococcus neoformans var. gattii serotype B, in an immunocompetent patient - Carlos da Silva LACAZ; Elisabeth Maria HEINS-VACCARI; Giovanna L. HERNÁNDEZ-ARRIAGADA; Eduardo Lacaz MARTINS; Célia A.L. PREARO; Simone Miwa CORIM; Marilena dos Anjos MARTINS (Universidade de São Paulo (USP), 2002)
The authors report a male patient, a seller with no detected immunosuppression, with an extensive ulcerated skin lesion localized on the left forearm, caused by Cryptococcus neoformans var. gattii serotype B. Oral treatment with fluconazole was successful. A review of the literature showed the rarity of this localization in HIV-negative patients. In contrast, skin lesions frequently occurs in HIV-positive patients, with Cryptococcus neoformans var. neoformans serotype A predominating as the etiological agent. In this paper, the pathogenicity of C. neoformans to skin lesions in patients immunocompromised or not, is discussed, showing the efficacy of fluconazole for the treatment of these processes.